Role of protein concentration on transient film thickness in synovial fluid lubricated joints. (December 2021) - Nissim, L.; Butt, H.; Gao, L.; Myant, C.; Hewson, R.
Abstract: A computational model of protein aggregation lubrication has been developed for predicting transient behaviour in lubricated prosthetics. The model uses an advection-diffusion equation to simulate protein transport in order to map concentration changes throughout the contact and inlet zones of an elasto-hydrodynamic contact. Concentration increases lead to exponential increase in fluid viscosity giving rise to lubricating film thicknesses an order of magnitude larger than would be expected using conventional elasto-hydrodynamic theory. The model parameters have been calibrated such that good agreement in transient film thickness is achieved with observed experimental results. Highlights: Protein aggregation in prosthetic joints can be modelled using simple assumptions EHL coupled with protein transport can achieve transient film thickness behaviour Flow rate attenuation is shown to recreate aggregation trends seen in experiments Fluid viscosity can be modelled as exponentially related to protein concentration